STIM and Orai isoform expression in pregnant human myometrium: a potential role in calcium signaling during pregnancy - Chin-Smith, Evonne C.; Slater, Donna M.; Johnson, Mark R.; Tribe, Rachel M. (Frontiers in Physiology, 2014)
Store-operated calcium (Ca2+) entry (SOCE) can be mediated by two novel proteins, STIM/Orai. We have previously demonstrated that members of the TRPC family, putative basal and store operated calcium entry channels, are present in human myometrium and regulated by labor associated stimuli IL-1β and mechanical stretch. Although STIM and Orai isoforms (1-3) have been reported in other smooth muscle cell types, there is little known about the expression or gestational regulation of STIM and Orai expression in human myometrium. Total RNA was isolated from lower segment human myometrial biopsies obtained at caesarean section from women at the time of preterm no labor (PTNL), preterm labor (PTL), term non-labor (TNL) and term with labor (TL); primary cultured human uterine smooth muscle cells, and a human myometrial cell line (hTERT-HM). STIM1-2, and Orai1-3 mRNA expression was assessed by quantitative real-time PCR. All five genes were expressed in myometrial tissue and cultured cells. Orai2 was the most abundant Orai isoform in human myometrium. Expression of STIM1-2/Orai1-3 did not alter with the onset of labor. Orai1 mRNA expression in cultured cells was enhanced by IL-1β treatment. This novel report of STIM1-2 and Orai1-3 mRNA expression in pregnant human myometrium and Orai1 regulation by IL-1β indicates a potential role for these proteins in calcium signaling in human myometrium during pregnancy.